Research on Methods Decreasing Pesticide Waste Based on Plant Protection Unmanned Aerial Vehicles: A Review - Hu, Heming; Kaizu, Yutaka; Huang, Jingjing; Furuhashi, Kenichi; Zhang, Hongduo; Li, Ming; Imou, Kenji (Frontiers in Plant Science, 2022)
Recently precision agriculture has become particularly important. In plant protection, the increasing maturity of unmanned aerial vehicle (UAV) technology has greatly increased efficiency. UAV can adapt to multiple terrains and does not require specific take-off platforms, it does well especially in some farmland areas with rugged terrain. However, due to the complex flow field at the bottom of the UAV, part of the droplets will not reach the surface of the plant which caused pesticides waste and environmental pollution. The droplet deposition is a good indicator for the utilization rate of pesticides, therefore this review described the recent studies for the droplet deposition to further methods improvement. Firstly, this review introduced the flight altitude, speed, and environmental factors that affect pesticide utilization efficiency, and then summarized methods to improve pesticide utilization efficiency from three aspects: nozzle, electrostatic spray, and variable spray system. We also pointed out the possible algorithm development direction of the drone's precision spray.